Perspective: an X-ray view of the coherent driving of materials - Steven L. Johnson; Urs Staub (npj Quantum Materials)
Abstract We discuss new opportunities in the study of materials arising from combining high intensity, phase-stable light pulses in the THz and mid-infrared with current and upcoming instrumentation at X-ray free electron laser (XFEL) facilities. We briefly summarize the relevant new technologies involved in making long-wavelength pump pulses, and upcoming advances in XFEL instrumentation. We also describe some initial key experiments in this quickly developing field, and provide an outlook.